Encyclopedia of applied spectroscopy - Andrews, David L., 1952- (Weinheim, Germany : Wiley-VCH, 2009)
The latest comprehensive reference set of spectroscopy and spectrographs, a must-have for all branches of physics in need of spectroscopy. Systematically covers theory, hardware and application. Covers the physics of spectroscopy with waves and particles of all kinds. Sections, abstracts and detailed tables of content allow for easy access.
Preface IX List of Contributors XI 1 Electromagnetic Radiation 1 Wendell T. Hill, III 2 Gamma-Ray Spectroscopy 27 Andrew M. Sandorfi, Christopher J. (Kim) Lister and Craig Woody 3 Mossbauer Spectroscopy 51 De-Ping Yang 4 X-Ray Spectroscopy 87 Thomas H. Markert and Eckhart Forster 5 Positron Spectroscopy 115 Paul G. Coleman 6 Muon Spectroscopy 153 Upali A. Jayasooriya and Roger Grinter 7 Neutron Spectroscopy 183 Anton Heidemann 8 Electron Scattering by Atoms, Ions, and Molecules 209 Klaus Bartschat, Philip G. Burke and Albert Crowe 9 Photoemission and Photoelectron Spectroscopy 283 Franz J. Himpsel and Ingolf Lindau 10 Ultraviolet and Visible Light Spectrometers 319 John L. Hardwick 11 Ultraviolet and Visible Absorption Spectroscopy 353 Robert H. Lipson 12 Colorimetry 381 Robert T. Marcus 13 Atomic Spectrometry and Elemental Analysis 421 Bernhard Welz and Daniel L.G. Borges 14 Molecular Fluorescence 477 Bernard Valeur 15 Resonance Energy Transfer 533 David L. Andrews and David S. Bradshaw 16 Optical Spectroscopy of Biological Materials 555 Valery V. Tuchin 17 Single-Molecule Fluorescence: Biophysics 627 Michael Prummer and Christian Hubner 18 Laser Sources 655 David L. Andrews and Robert H. Lipson 19 Linear Laser Spectroscopies 695 Stephen H. Ashworth 20 Photophysical and Photochemical Dynamics 717 Otto Horvath and Kenneth L. Stevenson 21 Condensed Phase Ultrafast Dynamics 747 Stephen R. Meech and Ismael A. Heisler 22 Ultrafast Spectroscopy 769 Oliver Kuhn and Stefan Lochbrunner 23 Surface Second Harmonic and Sum-Frequency Generation 817 Mitsumasa Iwamoto, Takaaki Manaka and Eunju Lim 24 Raman Scattering for Speciation and Analysis 833 Karen Esmonde-White, Mekhala Raghavan and Michael Morris 25 Spectrometers for Infrared Light 865 Yukihiro Ozaki and Shigeaki Morita 26 Infrared Molecular Vibrational Spectroscopy 887 Andrew B. Horn 27 Nuclear Magnetic Resonance Spectrometry 933 Vladimir I. Bakhmutov 28 Biomolecular Structures by Solution Nuclear Magnetic Resonance 963 Tharin M. A. Blumenschein 29 Mass Spectrometry 989 Jurgen H. Gross 30 Chromatography 1055 James M. Miller 31 Chemometrics and Multivariate Analysis 1103 Richard G. Brereton 32 Fourier and Other Mathematical Transforms 1149 Ronald N. Bracewell Glossary 1177 Index 1191
Includes bibliographical references and index.
Keywords: Spectrum analysis -- Encyclopedias